Report of colour polymorphism and range extension in two poorly known species of Indian Rhinophis (Squamata: Uropeltidae) - Venu, Govindappa; Balakrishna, Gandlahalli N.; Gadha, Leons K.; Raju, Narayanappa G.; Cyriac, Vivek P.; Seetharama, Halemane G.; Shampa, Chaudhary; Ramakrishna, Sompalem; Venkatachalaiah, Govindaiah; Ganesh, S.r. (Zootaxa, 2026)
We report new scalation, colour-pattern, and distributional data on two poorly known species of Rhinophis from India’s Western Ghats region. We report the first phenotypic data for a population of R. sanguineus from Ambalavayal in Wayanad, Kerala, India, including a highly distinct colour polymorphism. This polymorphism is characterised by syntopically occurring conspecifics of R. sanguineus having either the typical pattern of a uniform dorsum or a previously unreported distinctly cross-banded form. We observed multiple cross-banded morphotypes as young and adults, as well as males and females. We also report on a new population of R. karinthandani from Bhagamandala, in the Kodagu Plateau, nearly 70 km north of the previously known range in the Wayanad Plateau. This finding opens the prospects for inferred presence of R. karinthandani in a few of the intervening massifs as well. Our new finding of R. karinthandani also provides an extended range in known numbers of ventral scales for the species. Taken together, these findings underscore the incomplete knowledge on Indian Rhinophis, both old and recently described species, regarding multiple facets of natural history.